Shubnikov-de Haas Oscillation in the cubic Γ3-based heavy fermion superconductor PrV2Al20. (18th March 2015) - Shimura, Yasuyuki; Tsujimoto, Masaki; Sakai, Akito; Zeng, Bin; Balicas, Luis; Nakatsuji, Satoru
Abstract: PrV2 Al20 is the cubic Γ3 doublet system that exhibits strong hybridization effects and heavy fermion superconductivity. We measured the magnetoresistance using a high quality single crystal of PrV2 Al20 under the DC high magnetic field up to 35 T below ~ 0.4 K. We have succeeded in detecting the Shubnikov-de Haas (SdH) oscillation with a frequency of 250 T. Our analysis of this SdH oscillation yields the cyclotron effective mass ( m * c / m 0 ~ 5) and the mean-free path ( l = 170 Å).